(3HTQi GddHjH HPcQ GdMHjHs - (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s ((3RcQjG Hf jMji Hf RcQjG GdbQTi GdHdfSj s)
(3ChdgG (B:s
(3HYO GdMeO ddg Ydi Lejd GdGdBA adeG QhjJ bUjOI cYH Hf RgjQ (B((3HGfJ SYGO(B) (3jeOM HgG SjO GdeQSdjf BKQJ GdJHQc HgPG GdSdhc Ke hLOJ HYO Pdc ef CSeGFg Ydjg hSdGe afXeJ bUjOI ajgG s
(3BNQgG (B:s
(3PcQ CMGOjK JJYdb HGdeMHI ai Gddg , heMHI Gddg JYGdi , heMHI QShd Gddg Udi Gddg Ydjg hSde eG QCjJ ef GdfGS CMOG (B[(3jMH(B] (3cMH GUMGH eMemO eMeO GUdi Gddg Ydjg hSde BNQg hGdMeO ddg s
(3fSNI NGeSIs
(3Yf fSNI cJHgG Ndjd Hf CjHc GdUaOi hbQCgG Ydi GdeDdas
(3hHBNQgG SeGY dcKjQ ef GdCOHGAs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs